Psychedelic Harm Reduction and Integration: A Transtheoretical Model for Clinical Practice - Gorman, Ingmar; Nielson, Elizabeth M.; Molinar, Aja; Cassidy, Ksenia; Sabbagh, Jonathan (Frontiers in Psychology, 2021)
Psychedelic Harm Reduction and Integration (PHRI) is a transtheoretical and transdiagnostic clinical approach to working with patients who are using or considering using psychedelics in any context. The ongoing discussion of psychedelics in academic research and mainstream media, coupled with recent law enforcement deprioritization of psychedelics and compassionate use approvals for psychedelic-assisted therapy, make this model exceedingly timely. Given the prevalence of psychedelic use, the therapeutic potential of psychedelics, and the unique cultural and historical context in which psychedelics are placed, it is important that mental health providers have an understanding of the unique motivations, experiences, and needs of people who use them. PHRI incorporates elements of harm reduction psychotherapy and psychedelic-assisted psychotherapy, and can be applied in both brief and ongoing psychotherapy interactions. PHRI represents a shift away from assessment limited to untoward outcomes of psychedelic use and abstinence-based addiction treatment paradigms and toward a stance of compassionate, destigmatizing acceptance of patients’ choices. Considerations for assessment, preparation, and working with difficult experiences are presented.